Frequent loss of heterozygosity on the long arm of chromosome 6: identification of two distinct regions of deletion in childhood acute lymphoblastic leukemia1 - Takeuchi, Seisho; Koike, Michiaki; Seriu, Taku; Bartram, Claus R.; Schrappe, Martin; Reiter, Alfred; Park, Susan; Taub, Harry E.; Kubonishi, Ichiro; Miyoshi, Isao; Koeffler, H. Phillip (Cancer research, 1998)
Cytogenetic analysis of childhood acute lymphoblastic leukemia (ALL) identified nonrandom chromosomal abnormalities of the long arm of chromosome 6. Most of the alterations are deletions that are thought to be indicative of the presence of a tumor suppressor gene that is mutated on the remaining allele. These observations led us to consider whether 6q loss may contribute to the pathogenesis of childhood ALL. To define further a region containing this gene, we analyzed the loss of heterozygosity (LOH) of chromosome 6 in 113 primary ALL samples with matched normal DNA using 34 highly informative microsatellite markers. LOH was found in 17 (15%) samples at one or more of the loci, and partial or interstitial deletions of 6q were detected in 11 of these tumors. On the basis of these results, we performed a detailed deletional map and identified two distinct regions of deletion. The first region is flanked by D6S283 and D6S302 loci at 6q21-22. The second region is flanked by D6S275 and D6S283 loci at 6q21. Clinical analysis determined that LOH of 6q was demonstrated both in precursor-B cell ALLs (15 of 93; 16%) and in T cell ALLs (2 of 19; 11%). In addition, 19 patients have been studied at diagnosis and relapse; 18 showed the same 6q21-22 structural abnormality at relapse (normal, 16 patients; LOH, 2 patients) as their initial presentation, suggesting, albeit with a small patient sample size, that 6q21-22 deletions may be an initial event in leukemogenesis and may occur less frequently during the progression of childhood ALL. These data suggest the presence of putative tumor suppressor genes on chromosome arm 6q that are important in the development of both T and precursor-B childhood ALLs. Our map provides important information toward cloning putative ALL tumor suppressor genes.